Lingual epilepsia partialis continua in neurocysticercosis. (3rd January 2017) - Sureshbabu, Sachin; Nayak, Dinesh; Mittal, Gaurav; Peter, Sudhir; Sobhana, Chindripu; Aggarwal, Vikash
Abstract : A 60-year-old woman presented with focal clonic movements of her face and abnormal movements of her tongue for 5 months. An MRI revealed a ring enhancing lesion, suggestive of a cysticercal granuloma (figure 1). The patient was started on oxcarbazepine, which produced temporary control, with recurrence of jerky movements of her tongue lasting several minutes with frequent recurrence (videos 1 and 2 atNeurology.org ). EEG did not show focal abnormalities (figure 2). The episodes were aborted by levetiracetam, 1 g/d, and escalation of oxcarbazepine dose to 900 mg/d. Lingual epilepsia partialis continua occurs in Rasmussen encephalitis and herpes simplex encephalitis, but neurocysticercosis is an unusual cause. 1, 2